PERINGATAN DINI MASA STUDI DAN IPK MAHASISWA BERBASIS FRAMEWORK FOR APPLICATION OF SYSTEM THINKING - Nurjayadi Nurjayadi; Khusaeri Andesa; Torkis Nasution; Herwin Herwin (Universitas Islam Kuantan Singingi, 2020)
Universities must graduate students according to the curriculum that has been prepared, no later than 14 semesters, if they cannot be fulfilled, students must drop out. Based on graduation data for the last 3 years data on the number of graduations on time was found to be 60%. This means that this will reduce the achievements set out in the 2015-2020 Strategic Plan. If there is no structured and systematic effort, then there is the potential for graduation with an uncontrolled study period. Unfortunately, until now the system that has been built by PT has not been optimal can encourage students to graduate on time. Attempts to achieve timely graduation can be done by involving all lecturers, students, and academic implementing elements to monitor the academic track record of students since being registered as students. Monitoring of the student's academic track record includes attendance, independent assignments, structured assignments, practical assignments, library visits, consultations with PA, IP, and GPA lecturers. The results of supervision are measured at the minimum standard that must be achieved, by connecting all existing variables it can be concluded that the student can pass on time. The purpose of this study is to identify student track records, to connect with minimum standards that must be achieved, to conduct systems-based analysis so that an estimate of graduation performance is generated. Applications that will be generated are based on Framework for Application of System Thinking (FAST) that is good enough to provide early warning to students to graduate on time, and can monitor and monitor the value of discipline so as to prevent academic violations that affect the study period. FAST can analyze existing problems and can design the system. FAST has eight stages, where the first five stages are the stages of system analysis and the next three stages are the design stages. Applications are supported by means to disseminate information quickly and precisely, to fulfill it, use SMS and e-mail as a medium to transmit information from the system to students and academic advisers. If this application is implemented, it can give a warning to students before academic sanctions are issued.